Basics of viral marketing in the modern economy - Slivinska, Victoria (My University, 2014)
The term of "viral marketing," as an approach to sales, has been tied to the popularization of the notion that ideas spread like viruses. The field that developed around this notion, memetics, peaked in popularity in the 1990s. Viral marketing is a strategy that is used to encourage people to share a marketing message with others. Viral marketing strategies create mass exposure and influence for the marketing strategy.
Keywords: marketing; viral marketing; economy; економіка; вірусний маркетинг; маркетинг